Optimising prescribing practices in older adults with multimorbidity: a scoping review of guidelines - Penny Lun; Keng Teng Tan; Wendy Ang; Yasmin Munro; Felicia Law; Esther Ho (BMJ Open)
Objective Inappropriate polypharmacy occurs when multiple medications are prescribed without clear indications or where harms outweigh their benefits. The aims of this scoping review are to (1) identify prescribing guidelines that are available for older adults with multimorbidity and (2) to identify cross-cutting themes used in these guidelines.Design Scoping review.Data sources PubMed, Embase, Web of Science, the Cochrane Library databases, Cumulative Index to Nursing and Allied Health Literature, grey literature sources, six key geriatrics journals, and reference lists of identified review papers. The search was conducted in November 2018 and updated in September 2019.Study selection General prescribing guidelines tailored to or for adults including older adults with multimorbidity.Data extraction Data for publication description, guideline characteristics, information for users and criteria were extracted. The synthesis contains summarised qualitative descriptions of the studies and guideline characteristics as well as identified cross-cutting themes.Results Our search strategy yielded 10 427 unique citations, of which 70 fulfilled the inclusion criteria for synthesis. Among these, there were 61 unique guidelines and tools which used implicit, explicit, mixed or other approaches in the prescriber decision-making process. There are 11 cross-cutting themes identified in the guidelines. Prescriber-related themes are: conduct a comprehensive assessment before prescribing, identify patients’ needs, goals and priorities, adopt shared decision-making, consider evidence-based recommendations, use clinical prescribing tools, incorporate multidisciplinary inputs and embrace technology-enabled prescribing. Wider organisation-related and system-related themes related to education, training and the work environment are also identified.Conclusions From guidelines and tools identified, eleven cross-cutting themes provide a usable knowledge base when seeking to optimise prescribing among older adults with multimorbidity. Incorporating these themes in an approach that uses mixed criteria and implementation information could facilitate greater uptake of published prescribing recommendations.